Application of Microbial Fuel Cells for Leachate Bioremediation: The Effects of Nutrient Nourishment - Sholikah, Umi; Chosta, Fidela; Fiqar, Tegar Palyus; Anifah, Eka Masrifatus; Hudayarizka, Riza; Hibino, Tadashi (UI Scholars Hub, 2026)
Leachate contains a high organic content, which can cause environmental pollution. The organic content in leachate can be removed through bioremediation using microbial fuel cell (MFC) systems to remediate pollutants and generate bioelectricity. Organic matter is important to the MFC process as both a substrate and a nutrient source. This study investigated the effects of glucose and sodium phosphate buffer nourishment on BOD, COD, and TSS removal and bioelectricity generation. This study used leachate as a substrate and a graphite rod with a surface area of about 32.98 cm2 as an electrode. The reactor uses plastic blocks with a 3L capacity. Bioremediation using MFC was conducted in batch experiments under aerobic conditions for 20 days at various glucose dosages. All monitoring processes were conducted in real time using the internet of things (IoT). The glucose variations used were 10% (b/v) and 20% (b/v) with the addition of a sodium phosphate buffer. The removal efficiencies of BOD, COD, and TSS with 10% glucose and sodium phosphate buffer addition were 86.05%, 81.84%, and 75.50%, respectively. The highest electrical voltage was observed upon the addition of 20% glucose and sodium phosphate buffer at about 900 mV.